A randomised controlled trial and economic evaluation of a referrals facilitator between primary care and the voluntary sector. Issue 7232 (12th February 2000) - Grant, Clare; Goodenough, Trudy; Harvey, Ian; Hine, Chris
Abstract: Objectives: To compare outcome and resource utilisation among patients referred to the Amalthea Project, a liaison organisation that facilitates contact between voluntary organisations and patients in primary care, with patients receiving routine general practitioner care. Design: Randomised controlled trial with follow up at one and four months. Setting: 26 general practices in Avon. Participants: 161 patients identified by their general practitioner as having psychosocial problems. Main outcome measures: Primary outcomes were psychological wellbeing (assessed with the hospital anxiety and depression scale) and social support (assessed using the Duke-UNC functional social support questionnaire). Secondary outcomes were quality of life measures (the Dartmouth COOP/WONCA functional health assessment charts and the delighted-terrible faces scale), cost of contacts with the primary healthcare team and Amalthea Project, cost of prescribing in primary care, and cost of referrals to other agencies, over four months. Results: The Amalthea group showed significantly greater improvements in anxiety (average difference between groups after adjustment for baseline −1.9, 95% confidence interval −3.0 to −0.7), other emotional feelings (average adjusted difference −0.5, −0.8 to −0.2), ability to carry out everyday activities (−0.5, −0.8 to −0.2), feelings about general health (−0.4, −0.7 to −0.1), and quality of life (−0.5, −0.9 to −0.1). No difference was detected in depression or perceived social support. The mean cost was significantly greater in the Amalthea arm than the general practitioner care arm (£153 v £133, P=0.025). Conclusion: Referral to the Amalthea Project and subsequent contact with the voluntary sector results in clinically important benefits compared with usual general practitioner care in managing psychosocial problems, but at a higher cost.